2017
DOI: 10.2147/ijn.s128844
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanorod–based poly(lactic-co-glycolic acid) with manganese dioxide core–shell structured multifunctional nanoplatform for cancer theranostic applications

Abstract: Recently, photothermal therapy has become a promising strategy in tumor treatment. However, the therapeutic effect was seriously hampered by the low tissue penetration of laser. Therefore, in this study, radiofrequency (RF) with better tissue penetration was used for tumor hyperthermia. First, one type of gold nanorods (AuNRs) suitable for RF hyperthermia was selected. Then, poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) loaded with AuNRs and docetaxel (DTX) (PLGA/AuNR/DTX) NPs were constructed. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…In vivo rat experiments showed that the MnO 2 -, DOX-, and Ce6-loaded copolymer nanoparticle inhibited tumor growth effectively with an inhibition ratio of 92.35% (calculated by tumor weight), statistically (n =5 for each group) much higher than all 7 control groups. Wang et al 186 used PLGA to load gold nanorods (AuNRs) and DTX to form a PLGA/AuNR/DTX core, then coated it with MnO 2 ultrathin nanofilms. The higher GSH level in the tumor microenvironment caused the degradation of MnO 2 into Mn 2+ , enabling T 1 -MRI as well as controlled release of DTX at the tumor site.…”
Section: Copolymer-based Nanoparticles For Mr Cancer Theranosticsmentioning
confidence: 99%
“…In vivo rat experiments showed that the MnO 2 -, DOX-, and Ce6-loaded copolymer nanoparticle inhibited tumor growth effectively with an inhibition ratio of 92.35% (calculated by tumor weight), statistically (n =5 for each group) much higher than all 7 control groups. Wang et al 186 used PLGA to load gold nanorods (AuNRs) and DTX to form a PLGA/AuNR/DTX core, then coated it with MnO 2 ultrathin nanofilms. The higher GSH level in the tumor microenvironment caused the degradation of MnO 2 into Mn 2+ , enabling T 1 -MRI as well as controlled release of DTX at the tumor site.…”
Section: Copolymer-based Nanoparticles For Mr Cancer Theranosticsmentioning
confidence: 99%
“…Once the PSA antibody was detected, the hydrogen peroxide generated from the ELISA system etches the silver layer in the nanostructure, thus producing silver ions, leading to an enhanced photoacoustic signal at 780 nm 46 . Manganese(IV) oxide, MnO 2 47 , has also been of interest due to its ability to release small amounts of paramagnetic Mn 2+ ions, which can be used to enhance contrast in magnetic resonance imaging (MRI). However, elevated levels of Mn 2+ can cause a toxic effect in humans (manganism) so a greater understanding of the form (e.g., chelated or unchelated) in which these ions are released would be needed before this approach can be translated to the clinic.…”
Section: Encapsulation Methodsmentioning
confidence: 99%
“…Wang et al prepared PLGA nanoparticles loaded with GNRs and DTX (PLGA/ AuNR/DTX) and then coated the ultra-thin nanofilm with MnO 2 on the surface of it, constructing a new drug delivery system. Radiofrequency heating and MnO 2 degradation can significantly promote controlled drug release in tumor regions (Wang et al, 2017).…”
Section: Drug Release With Ph/nir Dual Responsementioning
confidence: 99%